Discovering presence as part of nurse educators' role modelling at a public nursing college in the North West province - Tiisetso A. Mofokeng; Emmerentia du Plessis; Kathleen Froneman (AOSIS, 2021)
Background: Nursing students learn the science and art of nursing, including presence, from classroom content, using skills in practice, or by watching an experienced nurse interact with a patient. Nursing education must be designed so that nursing students can construct the art and science of nursing practice. Nursing students must be educated to be sound practitioners in the 'being' of nursing practice. Nurse educators modelling presence to nursing students will improve the quality of patient care during clinical training and throughout their professional role. Aim: To explore and describe nurse educators' role modelling of presence to nursing students. Setting: This study was conducted at a public nursing college in the North West province. Methods: A qualitative, ethnographic study was conducted. Purposive sampling was used. Four nurse educators participated in the study and data saturation was reached. Data were collected through shadowing and informal reflective conversations over a period of 8 days. Results: The following relationships emerged: nurse educators model 'being professional', 'being facilitating, nurturing, caring and compassionate, encouraging, and motivating', and 'being purposeful in their nursing education approach'. Conclusion: Participants role modelled presence to nursing students despite daily challenges in their work. Contribution: Creating awareness of how nurse educators can model presence despite daily challenges in their work will influence and motivate nursing students to develop presence skills. This will have a positive impact on managing patients in practice. Recommendations can guide nursing education, policy development and future research to strengthen nurse educators modelling presence.